Personal protective equipment (PPE) and infection among healthcare workers – What is the evidence?. Issue 11 (9th September 2020) - Tian, Zixing; Stedman, Michael; Whyte, Martin; Anderson, Simon G.; Thomson, George; Heald, Adrian
Abstract: Background: The worldwide outbreak of coronavirus disease‐19 (COVID‐19) has already put healthcare workers (HCWs) at a high risk of infection. The question of how to give HCWs the best protection against infection is a priority. Methods: We searched systematic reviews and original studies in Medline (via Ovid) and Chinese Wan Fang digital database from inception to May, 2020, using terms 'coronavirus', 'health personnel', and 'personal protective equipment' to find evidence about the use of full‐body PPEs and other PPEs by HCW exposed highly infectious diseases. Results: Covering more of the body could provide better protection for HCWs. Of importance, it is not just the provision of PPE but the skills in donning and doffing of PPE that are important, this being a key time for potential transmission of pathogen to the HCW and in due time from them to others. In relation to face masks, the evidence indicates that a higher‐level specification of face masks and respirators (such as N95) seems to be essential to protect HCWs from coronavirus infection. In community setting, the use of masks in the case of well individuals could be beneficial. Evidence specifically around PPE and protection from the COVID‐19 virus is limited. Conclusion: Covering more of the body, and a higher‐level specification of masks and respirators could provide better protection for HCWs. Community mask usecould be beneficial. High quality studies still need to examine the protection of PPE against COVID‐19.